Pengaruh Kepemimpinan, Kompensasi Finansial dan Komunikasi terhadap Semangat Kerja - Budiasa, I Made; Susanti, Putu Herny (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
All-Business Cooperative (KSU) Kharisma Madani In Sesetan Denpasar is a cooperative that develops the quality of human resources. Where in doing a job requires a serious and competent spirit of work. This research was conducted by survey method by distributing questionnaires to employees of The All-Business Cooperative (KSU) Kharisma Madani in Sesetan Denpasar. The sample in the study was 51 employees. The sample is determined by the saturated sample method. After the validity and reliability test, the classical assumption test, then the data analysis using multiple linear regression analysis, t test, and f test. The results of the analysis showed that leadership has a positive and significant effect on morale, leadership has a positive and significant effect on morale, communication has a positive and significant effect on the spirit of work, obtained a calculated F value of 36,679 with a significant 0.000 < 0.05. The results of the double correlation analysis of 0.837 which means a very strong effect, while the value of the coefficient of determination is obtained 70.1% while the rest is 29.9%.